Gender Inequality: A Comparative Study of Participation in Technical Courses - Roslina Masud; Afizah Abdoll Mutalib; Izwah Ismail (RedWhite Press, 2018)
Technical Vocational Education Training (TVET) institutions play a crucial role in development of human capital required to transform the developing countries into fully developed nations. The technical skills acquire by the students are led by the industrial needs. However, technical courses are popular among the male students and only a small number of female students enroll into TVET institutions. This paper investigates the gender inequality issues and challenges in TVET education. A comparative study in terms of internship and promotions are included. Consequently, this paper also highlights on the technical and vocational career lines as an alternative pathway for TVET graduates to achieve career success and enhanced social inclusion through higher salaries, job status and educational attainment. The findings indicate that employability of the graduates were related to the individual’s strength and organization’s ability to appreciate, motivate and support the individuals in their career progression regardless the gender